Relationships between Body Size, Weight and Fecundity of the Endangered Fish Alburnus carinatus Battalgil, 1941 in the Manyas Lake (Turkey) - Gülşah SAÇ; Özcan GAYGUSUZ (Aquatic Sciences and Engineering, 2019)
Alburnus carinatus Battalgil, 1941 is an endangered fish species, which has a narrow distribution range in two shallow lake basins in northwest Anatolia. The present study aimed to describe the reproductive potential of this endemic fish with the relationships between body size, weight, and fecundity. A total of 101 female A. carinatus were captured from the Manyas Lake between January and June 2019. The standard length and body weight of these samples varied between 8.1– 15.0 cm and 9.38–65.45 g, respectively. The length-weight relationship of the female A. carinatus was calculated as W = 0.020 × SL2.959 (r2 = 0.866) with isometric growth. Absolute fecundity ranged from 1512 eggs (8.1 cm SL) to 3203 eggs (10.3 cm SL) with a mean of 2281 eggs (SD = 415.2). Fecundity–length relationship was F = 5.86 × SL2.67 (r2 = 0.702) and the fecundity–length relationship was F = 476.6 + 116.5 × L (r2 = 0.688). Mean relative fecundity was calculated as 244 eggs.cm−1 (SD = 34.1) (ranged from 179.8 to 310.9 eggs.cm−1) and 148 eggs.g−1 (SD = 14.9) (ranged from 115.1 to 171.8 eggs.g−1).